2011
DOI: 10.1007/s00018-011-0844-x
|View full text |Cite
|
Sign up to set email alerts
|

The dynorphin/κ-opioid receptor system and its role in psychiatric disorders

Abstract: The dynorphin/κ-opioid receptor system has been implicated in the pathogenesis and pathophysiology of several psychiatric disorders. In the present review, we present evidence indicating a key role for this system in modulating neurotransmission in brain circuits that subserve mood, motivation, and cognitive function. We overview the pharmacology, signaling, post-translational, post-transcriptional, transcriptional, epigenetic and cis regulation of the dynorphin/κ-opioid receptor system, and critically review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
144
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(148 citation statements)
references
References 448 publications
(595 reference statements)
2
144
0
1
Order By: Relevance
“…These inhibitory effects of κ opioid receptor agonists on cocaine-induced abuse-related behaviors are achieved potentially through the inhibition of dopamine release from dopaminergic neurons [18,19] . Dynorphin peptides, potent endogenous κ opioid recep- [20] , consist of dynorphin A (Dyn A), dynorphin A(1-8), dynorphin B (Dyn B), α-neoendorphin (α-Neo), β-neoendorphin (β-Neo), leumorphin, and big dynorphin (Big Dyn, which contains both Dyn A and Dyn B) [21] and have been found to modulate neuronal excitability and to regulate nociception, motivation, cognitive function and stress-induced mood disorders [22] .…”
Section: Introductionmentioning
confidence: 99%
“…These inhibitory effects of κ opioid receptor agonists on cocaine-induced abuse-related behaviors are achieved potentially through the inhibition of dopamine release from dopaminergic neurons [18,19] . Dynorphin peptides, potent endogenous κ opioid recep- [20] , consist of dynorphin A (Dyn A), dynorphin A(1-8), dynorphin B (Dyn B), α-neoendorphin (α-Neo), β-neoendorphin (β-Neo), leumorphin, and big dynorphin (Big Dyn, which contains both Dyn A and Dyn B) [21] and have been found to modulate neuronal excitability and to regulate nociception, motivation, cognitive function and stress-induced mood disorders [22] .…”
Section: Introductionmentioning
confidence: 99%
“…Dynorphin acting on kappa opioid receptors (KORs) is a powerful mediator of behavioral stress reactivity and negative effect (Bruchas et al, 2010;Tejeda et al, 2012;Van't Veer and Carlezon, 2013b). KORs are present in limbic and cortical regions involved in these functions, such as the medial prefrontal cortex (mPFC) and basolateral amygdala (BLA), and mPFC KORs may have a crucial role in anxiety and stress.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that KOR antagonists might have a wide range of indications, including the treatment of depressive-, anxiety-, and addictive disorders (for review, see Carlezon et al, 2009;Wee and Koob, 2010;Tejeda et al, 2012;Carlezon and Carroll, 2013). A general ability to reduce the impact of stress may explain how KOR antagonists can have efficacy in such a wide variety of animal models that would appear to represent different disease states Knoll and Carlezon, 2010;Van't Veer et al, 2012;Carlezon and Carroll, 2013).…”
Section: Introductionmentioning
confidence: 99%